In Situ Quantifying the Physical Parameters Determining the Efficiency of OLEDs Relying on Triplet–Triplet Annihilation Up‐Conversion. Issue 6 (30th January 2022) - Xiao, Shu; Qiao, Xianfeng; Lin, Chengwei; Chen, Liangjian; Guo, Runda; Lu, Ping; Wang, Lei; Ma, Dongge
Abstract: Triplet–triplet annihilation (TTA) up‐conversion is an effective way to utilize triplet excitons in organic light‐emitting diodes (OLEDs). However, the parameters characterizing the triplet excitons and relevant TTA process in OLEDs under working conditions have not been quantified. Here, an in situ method is established to map these parameters for further ascertaining their impact on device efficiency. The physical parameters, including triplet recombination rate, TTA rate, typical current J TTA, and saturated ratio, can be in situ quantified by transient electroluminescence technique. The expression of J TTA shows that minimizing the triplet quenching and maximizing the TTA rate are effective ways to lower J TTA . While highly efficient devices require a lower J TTA . Guided by these criteria, the device efficiency is promoted by weakening the triplet quenching via blending two materials. These investigations establish an in situ method to quantify the physical parameters that allow identifying the useful TTA materials and optimizing the design of device structures. Abstract : Triplet–triplet annihilation (TTA) bimolecular channel can bring two triplets into one singlet which can emit delay fluorescence. The proportion of the intensity of delay and prompt fluorescence is related to the rate constants of the two triplet consuming channels. Parameters determining the efficiency of TTA organic light‐emitting diodes can be deduced from this relation, and device efficiency can be improved guided by these parameters.